The Complexity of Oxidative Stress in Human Age-Related Diseases—A Review - Alicja Płóciniczak; Ewelina Bukowska-Olech; Ewa Wysocka (Metabolites)
The aging process is a complex and dynamic phenomenon influenced by genetic, environmental, and biochemical factors. One of the key contributors to aging and age-related diseases is oxidative stress, resulting from an imbalance between the generation of reactive oxygen species (ROS) and the efficiency of antioxidant defense systems. In this review, we introduce the concept of the oxidative stress complexity—a network encompassing ROS-generating systems, enzymatic and non-enzymatic antioxidants, and genetic determinants that collectively shape redox homeostasis. Emerging research highlights the significant influence of genetic variability on the activity and expression of selected and most examined antioxidant enzymes, including superoxide dismutase (SOD), paraoxonase 1 (PON1), catalase (CAT), and glutathione peroxidase (GPX), thereby modulating individual susceptibility to oxidative damage, disease onset, and the pace of aging. Particular attention is paid to the interplay among oxidative stress, chronic inflammation, and metabolic dysfunction in the pathogenesis of various age-related disorders. By integrating findings from molecular studies, clinical research, and population genetics, we discuss the diagnostic and prognostic potential of antioxidant enzymes as biomarkers of aging and explore strategies for redox-modulating interventions. Understanding these interrelations is essential for identifying biomarkers of biological aging and developing personalized strategies aimed at promoting healthy aging and reducing the risk of chronic disease.